Terpenoids from Adiantum emarginatum - Kiem et al, Phan Van (Vietnam Journal of Chemistry, 2014)
From the petroleum ether fraction of the methanolic extract of Adiantum emarginatum Bory, three triterpenoids including tetrahymanol (1), isoadiantol B (2), hydroxyadiantone (3), and a diterpenoid 8,13-epoxy-14-labden-19-oic acid (4) have been isolated. Their structures were deduced from the spectral evidence and on the basis of X-ray diffraction studies.